ØªØ·Ø¨ÙŠÙ‚ Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¥Ù†ØªÙ‚Ø§Ø¦ÙŠØ© Ù„ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… (Ø¯Ø±Ø§Ø³Ø© ÙƒÙŠÙÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù†ÙŠ ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø³Ù„ÙÙŠØ© Ø§Ù„Ø´Ø§ÙØ¹ÙŠØ© Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ Ø¬Ø§ÙˆÙ‰ Ø§Ù„Ø´Ø±Ù‚ÙŠØ©) - Nisa Nurdini; Mahmud Fauzi (Program Studi Pendidikan Bahasa Arab, 2020)
Speaking skills are a person’s ability to express voice or words to express thought and ideas and convey feelings to the speakr’s partner in a very broad situation and can be understood by the listener. Therefore, a teacher has to care about this speaking skill. In oder that these students can be successfully master the language I speaking. However, the teacher never considers the importance of a tool in the from of a method in the teaching process. So they use methods that are not suitable for the situation of students in the class. As a result, students feel bored, sleepy when learning Arabic. Combined method is a solution for not getting bored and great for helping students in learning Arabic. By using the combined method, a teacher is very free when teaching. Because the teacher is not focused on one method only but also teachers can be more creative to incorporate some methods in order that students feel excited when learning Arabic.